Reinterpretation of the Rights and Duties of Contemporary Husbands and Wives - Ja'far, A. Kumedi; Hermanto, Agus (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
A concept of rights and obligations will work when there is a balance between the two. Malahat theory is an intra doctrinal reform for the realization of humane legal norms. However, in reality, this concept is not easy to implement. It is said that a woman is made as to the subordinate in the family and sometimes there is no justice for her. At this time, women not only play a role as housewives but also help earn money for the family. What becomes a problem is how to reinterpret the equitable distribution of household rights and obligations. This study aims to describe the rights and obligations of husband and wife by maintaining the values of justice. This research is library research that discusses the husband's income for his wife, who is also the breadwinner. The paradigm of the husband is the leader of the household, and the wife is the housewife is something that spurs Muslim feminists to reinterpret. It is because wives are no longer only responsible as housewives, but more than that, they also help make a living in the household. Then, the concepts of justice, equality, ukhuwah islamiyah and mu'asyarah bil ma'ruf must be prioritized for the benefit and the formation of a sakinah, mawaddah wa rahmah in a family. It needs to be reconsidered if we want to make it a new fiqhparadigm.